Hard collar immobilisation following elective surgery on the cervical spine: a cross-sectional survey of UK spinal surgeons. (3rd September 2022) - Brannigan, Jamie F. M.; Mowforth, Oliver D.; Francis, Jibin J.; Budu, Alexandru; Laing, Rodney J.; Davies, Benjamin M.
Abstract: Introduction: Although mostly used in the management of spinal trauma, hard collar immobilisation is also used as an adjunct to recovery after elective cervical spine surgery. Many surgeons believe that bracing reduces the risk of non-union and pain and provides a subjective sense of security for patients. There is little if any, evidence for this practice and immobilisation can be a direct cause of adverse events. The primary aim of this study was to provide an updated assessment of post-operative bracing practice in UK spinal surgeons, including the indications, rationale and perspectives on compliance and complications. Methods: Neurosurgeons and spinal orthopaedic surgeons completed a web-based survey distributed by email to members of the Society of British Neurological Surgeons (SBNS) and the British Association of Spinal Surgeons (BASS). Professional information captured included level of experience and whether surgeons had a specialist interest in spinal surgery. Questions first focused on the frequency and duration of hard collar immobilisation for common decompressive procedures. Later questions captured surgeon rationale, perceptions of patient compliance, complications, and collar removal. Results: A total of 86 surgeons completed the survey, of whom 83% were spinal specialists. In total, 33 (38%) surgeons recommend a hard collar following at least one of the elective procedures listed. Collars were most commonly recommended following cervical corpectomy (30%). The support of fusion and bone healing was the most common rationale (82%), with post-operative pain (45%) and limiting patient activity (39%) also considered. Most surgeons (69%) believed that their patients were compliant. All listed types of complications were reported, with impaired activities of daily living (41%) and impaired sleep (34%) the most frequently cited. Conclusions: Current post-operative use of hard collars is much lower in the United Kingdom than previously reported in the United States. Surgeon decision-making is inconsistent and may benefit from greater standardisation. Future work is needed to help develop guidelines as a move away from arbitrary to evidence-based practice.